The Influence Of Service Quality On Customer Satisfaction at PT. PLN Mattoanging Customer Service Unit In Makassar - Nurlinda, Nurlinda; Alam, Andi Rifqah Purnama; Anggreni, Dewi; Sofiansyah, Nurul (Economos : Jurnal Ekonomi dan Bisnis, 2024)
This research was conducted at PT. PLN Mattoanging Customer Service Unit, located at Jalan Monginsidi No. 2, Makassar City, over a period of two months. The research data was obtained from two sources, primary data and secondary data. Primary data was gathered through questionnaires, observations, and interviews with customers, while secondary data was collected from report documents, relevant regulations, and interview results. The data collection method involved observation techniques to obtain preliminary information, questionnaires to capture respondents' written responses, and literature studies to support the investigation related to customer loyalty. The sample size for this study consisted of 100 respondents. The data analysis method involved descriptive analysis to describe the data obtained from the questionnaires, as well as simple linear regression analysis to estimate the relationship between the independent variable (service quality) and the dependent variable (customer satisfaction). The results of the linear regression data analysis showed that y = 2.928 + 0.200x, with a correlation coefficient of 0.765 and a coefficient of determination (r²) of 0.5863 or 58.63%. From the t-test hypothesis testing, it was found that t-count = 12.0221 > t-table = 1.65993. Based on these results, it can be concluded that customer satisfaction is significantly and positively influenced by the service quality of PT. PLN Mattoanging Customer Service Unit in Makassar. Thus, the findings of this research are acceptable.